2012
DOI: 10.1007/bf03325333
|View full text |Cite
|
Sign up to set email alerts
|

Diet type and changes in food cravings following weight loss: Findings from the POUNDS LOST Trial

Abstract: Few well-controlled trials have evaluated the effects that macronutrient composition has on changes in food cravings during weight loss treatment. The present study, which was part of the POUNDS LOST trial, investigated whether the fat and protein content of four different diets affected changes in specific food cravings in overweight and obese adults. A sample of 811 adults were recruited across two clinical sites, and each participant was randomly assigned to one of four macronutrient prescriptions: (1) Low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 22 publications
3
29
0
Order By: Relevance
“…Consistent with previous literature (Anton et al, 2012; Martin et al, 2006, 2011), diet restriction and food craving showed similar patterns of reduction during the active (weekly) treatment period. Importantly, from baseline to 6 months, higher levels of initial food craving predicted less steep declines in BMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous literature (Anton et al, 2012; Martin et al, 2006, 2011), diet restriction and food craving showed similar patterns of reduction during the active (weekly) treatment period. Importantly, from baseline to 6 months, higher levels of initial food craving predicted less steep declines in BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Longitudinal evidence has also reported relationships between food cravings, energy intake, and BMI, with experimental evidence suggesting that caloric restriction is related to decreased food cravings and weight loss decreased food cravings (Anton et al, 2012; Martin et al, 2011). The experimental evidence suggests that changes in food intake may actually influence food cravings.…”
Section: Introductionmentioning
confidence: 97%
“…However, the interventions were substantially heterogeneous. For instance, subjects in some study arms were instructed and provided resources to restrict their energy intake by a certain number of calories 2325 or by a percentage of their estimated energy intake 18 , while participants of other studies were given a specific type of a diet to follow (e.g. low-fat 17, 24 , low-carbohydrate 17, 19 , high carbohydrate and protein 19 , vegetarian 24 ) in addition to restricting their overall energy intake.…”
Section: Resultsmentioning
confidence: 99%
“…low-fat 17, 24 , low-carbohydrate 17, 19 , high carbohydrate and protein 19 , vegetarian 24 ) in addition to restricting their overall energy intake. The energy deficit also varied from low-calorie diets 1519, 2325 to very-low calorie diets 15, 16 . Females outnumbered males in all studies that reported the male: female ratio.…”
Section: Resultsmentioning
confidence: 99%
“…The largest single study to date to examine the question of diet composition is the POUNDS Lost trial (12, [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. In this 2-year dietary intervention, 811 individuals who were overweight or obese were randomly assigned in a 2×2 factorial design to one of the four diets with target intakes of 15% (average protein = AP) or 25% protein (high protein = HP) and 20% fat (low fat = LF) or 40% fat (high fat = HF).…”
Section: Introductionmentioning
confidence: 99%